Narratives from Africa and the Diaspora: Filmaking in Africa (Readings, Concerts and other events, 2023)
In April 2023 the Africa Multiple Cluster of Excellence hosted this conversation with filmmaker Jean-Pierre Bekolo and scholar Alexie Tcheuyap at @kunst-undkulturhausneunein8931. Jean-Pierre Bekolo is a filmmaker from Cameroon. He is considered to be one of the avant-garde filmmakers from the continent with a large oeuvre of 30 years suggesting each time new topics and new approaches to film genres and narrative modes. Alexie Tcheuyap is Professor of French and Postcolonial Studies at the University of Toronto, where is hold the position of Associate Vice-President & Vice-Provost. He has published extensively on the subject of African literatures, film and media, and is a member of the Royal Society of Canada.